PEDAGOGICAL CONDITIONS FOR CREATIVE SELF-DEVELOPMENT OF THE FUTURE SPECIALIST IN PROCESS OF LEARNING (Pedagogy of Higher and Secondary Education, 2004)
In this article the author examines the most effective pedagogical conditions of Creative self development of a feature specialist at a higher educational establishment.